Economic Evaluation of Intergenerational Programs: Suggested Measures and Design. Issue 4 (2nd October 2021) - Vecchio, N.; Comans, T.; Harris, P.; Graham, V.; Cully, A.; Harris, N.; Fitzgerald, J.; Cartmel, J.; Golenko, X.; Radford, K.
ABSTRACT: Multiple aspects of intergenerational programs present challenges for evaluators. Broader measures and perspectives are needed particularly with respect to informing economic evaluations of intergenerational programs. The study aims to (1) Identify impact measures suitable for an economic evaluation of a mixed generation program; (2) Design an economic evaluation that compares these program impacts with current services. The suggested evaluation design includes perspectives from children, parents, adult care recipients, caregivers and service providers. Measures for inclusion were based on the literature and selected using a set of criteria and stakeholder interviews. To inform economic evaluations of mixed generation programs we recommend a quasi-experimental design using measures of experience/satisfaction, quality of life/wellbeing, willingness to pay, burden of care and service utilization. The suggested economic evaluation measures and design will guide future programs of mixed generations in the pursuit of cost-effective and sustainable service options in this rapidly evolving service environment.